Smart Doors For Monitoring Body Temperature And Space Capacity Based On IoT - Ady Alfian; Triyanto Pangaribowo (Journal of Electronics Technology Exploration, 2023)
Presently, multiple countries are engaged in combatting virus outbreaks transmitted through contact with infected individuals. To address this issue, several measures have been taken to shift the pandemic status to an endemic state. This study introduces an Internet of Things (IoT) device designed to monitor body temperature and room occupancy in real-time. Notifications are sent when a room surpasses its capacity or when body temperature exceeds the allowable threshold. The system enables real-time alerts and stores data for remote accessibility and analysis. The experiments conducted involve Infra Red Proximity, temperature sensor (MLX90614), object distance sensor (HCSR04), Wemos, and Solenoid Door Lock. Telegram is used as the medium for data transmission. The developed system proves effective in continuously monitoring body temperature and room occupancy.